Balancing the Scales: Kuwait's Neutrality Amidst Geopolitical Rivalries in a F(r)actious Middle East - Kirkhope-Arkley, Joshua (The Columbia Journal of Asia, 2022)
The Middle East as a geopolitical region is not generally renowned for the neutrality and mediation present in its politics. Kuwait defies this trend, acting as a mediator in some conflicts and remaining neutral in others. When it seems as though Kuwait is taking a tough, sided stance (for example, its steadfast refusal to recognise the State of Israel), further analysis proves that the supposedly unneutral position is in fact a way of remaining neutral in another conflict. Through a “micro-to-macro” approach analysing Kuwaiti foreign policy first within the GCC, then within the Middle East, then on a global level, this essay has been able to examine and explain the Emirate’s foreign policy, to shed light on a country often unfairly overlooked due to its size and perceived lack of importance. Its foreign policy of neutrality, multilateralism, and mediation, however, is exactly what makes Kuwait so significant on the world stage.